PENGARUH PENGGUNAAN FACEBOOK TERHADAP PERILAKU CYBERBULLYING DI KALANGAN REMAJA DESA MANTINGAN KECAMATAN TAHUNAN KABUPATEN JEPARA - Mahfudlah Fajrie; Noor Syaidah (An-Nida : Jurnal Komunikasi Islam, 2019)
This research aimed the influenceof using facebook toward cyberbullying behavior. The hypothesis in this research wasthere was an influenceof using facebook toward cyberbullying behavior among village adolescentsMantingan. Subject in this research were 61 adolescents in aged range 15-17 years old consist of 30 boys adolescents and 31 girls adolescents. The sampling technique used was proportional sampling. Method of collecting data consist of observation, interview, and questionnaire. The data was analyzed using aplikation IBM SPSS Statistics 25. Result of test correlation using correlation product moment between using facebook with cyberbullying behavior was 0,964 with value significant 0,000, which means there was a significant positive between using facebook toward cyberbullying behavior among village adolescents Mantingan.